The Biosorption of Copper(II) Using a Natural Biofilm Formed on the Stones from the Metro River, Malang City, Indonesia - Kurniawan, Andi; Ulfa, Siti Mariyah; Chamidah, Chamidah (International Journal of Microbiology, 2022)
Biofilm is the predominant habitat of microbes in aquatic ecosystems. Microhabitat inside the biofilm matrix is a nutrient-rich environment promoted by the adsorption of nutrient ions from the surrounding water. Biofilms can not only adsorb ions that are nutrients but also other ions, such as heavy metals. The ability of biofilm to attract and retain heavy metals, such as copper(II), makes biofilms a promising biosorbent for water pollution treatment. The present study analyzes the characteristics of copper(II) adsorption by biofilms naturally formed in the river. The biofilms used in this study grow naturally on the stones in the Metro River in Malang City, Indonesia. Methods to analyze the adsorption characteristics of copper(II) by biofilms were kinetics of the adsorption and adsorption isotherm. The maximum adsorption amount and the adsorption equilibrium constant were calculated using a variant of the Langmuir isotherm model. In addition, the presence of the functional groups as suggested binding sites in biofilm polymers was investigated using the Fourier transform infrared (FTIR) analysis. The results indicate that copper(II)’s adsorption to the biofilm is a physicochemical process. The adsorption of copper(II) is fitted well with the Langmuir isotherm model, suggesting that the adsorption of copper(II) to a biofilm is due to the interaction between the adsorption sites on the biofilm and the ions. The biofilm’s maximum absorption capacity for copper(II) is calculated to be 2.14 mg/wet-g of biofilm, with the equilibrium rate constant at 0.05 L/mg. Therefore, the biofilms on the stones from river can be a promising biosorbent of copper(II) pollution in aquatic ecosystems.